Adverse events following immunization associated with coronavirus disease 2019 (COVID-19) vaccines: A descriptive analysis from VigiAccess - Peter Yamoah; Kofi Boamah Mensah; Joseph Attakorah; Neelaveni Padayachee; Frasia Oosthuizen; Varsha Bangalee (Taylor & Francis Group, 2022)
This study assessed adverse events following immunizations (AEFIs) reported on COVID-19 vaccines in VigiAccess and determined the reporting trends across all continents of the world. The study was cross-sectional quantitative in design. VigiAccess was searched on 10 November 10 2021 for reported adverse events following the introduction of COVID-19 vaccines. After entering the search term, "COVID-19 vaccines" in VigiAccess, AEFIs associated with nine approved brands of COVID-19 vaccines had been documented in the database. Data were captured among age groups, sex, and continents of the world and analyzed using Statistical Package for Social Sciences (SPSS) version 25. Overall, 2,457,386 AEFIs had been reported in VigiAccess at the time of the search. No causal associations could be established between the vaccines and the AEFIs. The public accessing VigiAccess data should therefore be made aware of this in order to not falsely attribute AEFIs to COVID-19 vaccines when assessing the database.